Rural Homelessness: Prevention Practices in Wales. Issue 1 (January 2020) - Gibbons, Andrea; Madoc-Jones, Iolo; Ahmed, Anya; Jones, Katy; Rogers, Michaela; Wilding, Mark
Abstract : Homelessness is largely understood as an urban issue and so rural homelessness is to a large extent invisible in both academic literature and in policy and practice discussions, just as it is often invisible in discourses of everyday rural life. This article draws on extensive interviews with homeless service users and providers in three rural authorities in Wales to give a clearer sense of the nature and challenges of rural homelessness. The article documents and explores the very different strategies employed by those facing homelessness in the rural context, as well as those of rural local authorities providing them preventative and person-centred support. Analysis of the struggle of many rural households to remain in place, often at the cost of homelessness and lowered ability to access services, will have resonance in a range of contexts and have implications for policy makers and practitioners in rural contexts beyond Wales.